Peran Guru dalam Membentuk Jiwa Kewirausahaan Siswa melalui Program Business Day di SDI Baiturrahman Bagor - Siti Ismi Wulandari; Arif Mansyuri; Nur Kholis (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
The Indonesian economy is facing serious challenges such as financial instability, high unemployment and the threat of a middle income trap. To overcome this, it is necessary to develop human resources that are oriented towards entrepreneurship. Education is the key in creating creative, innovative and tough individuals. This research aims to examine the role of teachers in forming students' entrepreneurial spirit through the "Business Day" extracurricular program at SDI Baiturrahman Bagor. This research uses a qualitative approach method with analyzing materials, observations and interviews with sources. This research identifies three main roles of teachers, first the teacher as a learning facilitator, second the teacher as a mentor, and finally the teacher as an evaluator. This research aims at the active role of teachers in implementing the program to foster students' entrepreneurial spirit.